Airbnb and micro‐entrepreneurship in regional economies: Lessons from Australia. (12th September 2021) - Mahmuda, Sirat; Sigler, Thomas; Corcoran, Jonathan; Knight, Eric
Abstract: Having begun as a short‐term rental platform in major cities, Airbnb has now extended to many remote and regional areas of Australia. One effect of this spread has been disruption to the conventional rental industry, which stimulates micro‐entrepreneurship in local communities directly through short‐term accommodation and indirectly through related industries. Given Australia's core–periphery settlement structure, resulting from the country's historical development, disruption through entrepreneurship has relatively more potential in remote and regional areas. This article uses the Porter diamond model to explain how Airbnb‐led micro‐entrepreneurship interacts with territorially embedded socioeconomic characteristics across regional and remote Australia. Drawing on Airbnb data for Australia between 2014 and 2018 at the scale of regional labour markets, we use a quantile regression model to explain the association between Airbnb‐led micro‐entrepreneurship and four distinct structural dimensions between metropolitan and non‐metropolitan regions. The analysis provides evidence that non‐metropolitan regions have certain stronger competitive advantages for attracting Airbnb‐led micro‐entrepreneurship compared with metropolitan regions, particularly across regional cities and in areas associated with mining, agriculture, and tourism. We conclude that policymakers should weigh concerns relating to peer‐to‐peer accommodation in major metropolitan regions against the purported benefits to peripheral regions. Abstract : The analysis provides evidence that non‐metropolitan regions have certain stronger competitive advantages for attracting Airbnb‐led micro‐entrepreneurship compared with metropolitan regions, particularly across regional cities and in areas associated with Mining, Agriculture and Tourism. The paper makes the argument that regions benefit from the P2P economy is ways that urban areas do not, and may provide opportunities for economic development where embedded systems overlook certain potential.